all equations of the type ax^2+bx+c=0 can be resolved using the quadratic formula: \frac-b±\sqrtb^2-4ac2a. The quadratic formula provides two solutions, one when ± is addition and one as soon as it is subtraction.

You are watching: Which are the solutions of the quadratic equation? x2 = 9x + 6


This equation is in conventional form: ax^2+bx+c=0. Substitute 1 for a, 9 for b, and also -6 for c in the quadratic formula, \frac-b±\sqrtb^2-4ac2a.
*

3x2+9x-6=0 Two remedies were uncovered : x =(-3-√17)/2=-3.562 x =(-3+√17)/2= 0.562 step by action solution : action 1 :Equation at the end of step 1 : (3x2 + 9x) - 6 = 0 step 2 : step 3 ...
\displaystylex=\left\lbrace-2,\frac12\right\rbrace Explanation: \displaystyle6x^2+9x-6=0\displaystyle\textsolution 1:\displaystyle\textfactor the equation : ...
-x2+9x-6=0 Two remedies were uncovered : x =(-9-√57)/-2= 8.275 x =(-9+√57)/-2= 0.725 action by step solution : step 1 : step 2 :Pulling out like terms : 2.1 pull out choose factors : ...
-3x2+9x-6=0 Two remedies were found : x = 2 x = 1 step by step solution : step 1 :Equation at the end of step 1 : ((0 - 3x2) + 9x) - 6 = 0 action 2 : step 3 :Pulling out choose terms : ...
2x2+x-6=0 Two remedies were uncovered : x = -2 x = 3/2 = 1.500 step by action solution : step 1 :Equation at the end of action 1 : (2x2 + x) - 6 = 0 action 2 :Trying to aspect by dividing the ...
3x2+x-6=0 Two remedies were uncovered : x =(-1-√73)/6=-1.591 x =(-1+√73)/6= 1.257 step by action solution : step 1 :Equation in ~ the end of step 1 : (3x2 + x) - 6 = 0 action 2 :Trying to element ...
More Items
*
*

*
*
*

All equations that the kind ax^2+bx+c=0 can be addressed using the quadratic formula: \frac-b±\sqrtb^2-4ac2a. The quadratic formula offers two solutions, one when ± is addition and one once it is subtraction.
This equation is in traditional form: ax^2+bx+c=0. Instead of 1 for a, 9 because that b, and also -6 for c in the quadratic formula, \frac-b±\sqrtb^2-4ac2a.
Quadratic equations such as this one can be fixed by perfect the square. In order to finish the square, the equation must very first be in the type x^2+bx=c.
Divide 9, the coefficient that the x term, by 2 to obtain \frac92. Then add the square of \frac92 come both sides of the equation. This step makes the left hand side of the equation a perfect square.
Factor x^2+9x+\frac814. In general, once x^2+bx+c is a perfect square, the can constantly be factored as \left(x+\fracb2\right)^2.

See more: Physical Appearance Of An Organism, Genetics Flashcards


Quadratic equations such as this one have the right to be resolved by a new direct factoring method that go not need guess work. To use the straight factoring method, the equation must be in the form x^2+Bx+C=0.
Let r and also s it is in the determinants for the quadratic equation such the x^2+Bx+C=(x−r)(x−s) where sum of factors (r+s)=−B and also the product of factors rs = C
Two number r and also s amount up come -9 precisely when the mean of the 2 numbers is \frac12*-9 = -\frac92. You can likewise see that the midpoint the r and also s corresponds to the axis of the contrary of the parabola represented by the quadratic equation y=x^2+Bx+C. The values of r and s space equidistant indigenous the facility by an unknown amount u. Express r and s with respect to variable u.
*
*

EnglishDeutschEspañolFrançaisItalianoPortuguêsРусский简体中文繁體中文Bahasa MelayuBahasa Indonesiaالعربية日本語TürkçePolskiעבריתČeštinaNederlandsMagyar Nyelv한국어SlovenčinaไทยελληνικάRomânăTiếng Việtहिन्दीঅসমীয়াবাংলাગુજરાતીಕನ್ನಡकोंकणीമലയാളംमराठीଓଡ଼ିଆਪੰਜਾਬੀதமிழ்తెలుగు